THE IMPACT OF FATHERLESS ON STUDENTS' LEARNING ACHIEVEMENT IN PRIMARY SCHOOL X BOYOLALI CITY - Berlian, Toti Cahya (Melekliterasi Press, 2023)
Students learning achievements at school will certainly not be separated from family interference, especially significant others, namely father and mother. Family is the smallest group of human life which generally consists of father, mother and children. The role of parents in parenting is very influential for children. Not only mothers, father figures are also very important in terms of parenting. Not only is he obliged to earn a living and meet living expenses, fathers also have a role and obligation to educate their children. The absence of the father's role referred to here is the physical and psychological absence in the child's life. Known by the terms fatherless, father absence, father loss or father hunger. The physical absence of a father's role can be caused by death, departure, divorce, and other family problems. Fatherlessness is the absence of a father's role and figure in a child's life. Because we know that fatherlessness has a big influence on children's psychology, which can result in children becoming often moody, having difficulty concentrating, which ultimately results in their learning achievement decreasing